Bone marrow mesenchymal stem cells offer an immune-privileged niche to Cutibacterium acnes in case of implant-associated osteomyelitis. (1st January 2022) - Dubus, M.; Varin, J.; Papa, S.; Chevrier, J.; Quilès, F.; Francius, G.; Audonnet, S.; Mauprivez, C.; Gangloff, S.C.; Siboni, R.; Ohl, X.; Reffuveille, F.; et al.
Abstract: Considered as some of the most devastating complications, Cutibacterium acnes ( C. acnes )-related osteomyelitis are among the hardest infections to diagnose and treat. Mesenchymal stem cells (MSCs) secrete number of immunomodulatory and antimicrobial soluble factors, making them an attractive treatment for bacterial infection. In this study, we examined MSCs/ C. acnes interaction and analyzed the subsequent MSCs and bacteria's behaviors. Human bone marrow-derived MSCs were infected by C. acnes clinical strain harvested from non-infected bone site. Following 3 h of interaction, around 4% of bacteria were found in the intracellular compartment. Infected MSCs increased the secretion of prostaglandin E2 and indolamine 2, 3 dioxygenase immunomodulatory mediators. Viable intracellular bacteria analyzed by infrared spectroscopy and atomic force microscopy revealed deep modifications in the wall features. In comparison with unchallenged bacteria, the viable intracellular bacteria showed (i) an increase in biofilm formation on orthopaedical-based materials, (ii) an increase in the invasiveness of osteoblasts and (iii) persistence in macrophage, suggesting the acquisition of virulence factors. Overall, these results showed a direct impact of C. acnes on bone marrow-derived MSCs, suggesting that blocking the C. acnes /MSCs interactions may represent an important new approach to manage chronic osteomyelitis infections. Statement of significance: The interaction of bone commensal C. acnes with bone marrow mesenchymal stem cells induces modifications in C. acnes wall characteristics. These bacteria increased (i) the biofilm formation on orthopaedical-based materials, (ii) the invasiveness of bone forming cells and (iii) the resistance to macrophage clearance through the modification of the wall nano-features and/or the increase in catalase production. Graphical abstract: Image, graphical abstract